2011
DOI: 10.1002/nau.21039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of female urinary incontinence and urgency on women's and their partners' sexual life

Abstract: Female UI and urgency negatively affected sexual life in almost half of the women and in every fifth partner. A need for information and advice concerning sexual issues due to the woman's urinary disorder was found in one fifth of the couples. The majority of women with urinary leakage during sexual activities considered this as a problem, but most of their partners did not. Overall, the concordance of the answers within the couples was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
7
22
0
2
Order By: Relevance
“…20,21 Coital incontinence is directly associated with sexual dysfunction. 22 In this study, improvement in sexual functions has been observed in women after treatment of UI, which is in agreement with the literature. 23 ICIQ-LUTSqol revealed good discriminant validity in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20,21 Coital incontinence is directly associated with sexual dysfunction. 22 In this study, improvement in sexual functions has been observed in women after treatment of UI, which is in agreement with the literature. 23 ICIQ-LUTSqol revealed good discriminant validity in this study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the duration and severity of UI may not be correlated with the adverse effects on sexual functions 20,21 . Coital incontinence is directly associated with sexual dysfunction 22 . In this study, improvement in sexual functions has been observed in women after treatment of UI, which is in agreement with the literature 23…”
Section: Discussionsupporting
confidence: 90%
“…Most of them showed that UI adversely affects women's sexual life, mental health, and social life [21][22][23]. We observed decreased prevalence of UI in sexually active respondents.…”
Section: Discussionmentioning
confidence: 50%
“…Sixty four patients (aged [16][17][18][19][20][21][22][23][24] Twenty eight respondents (44%) reported being urine incontinent. There were no differences in age, BMI, FEV1, CFRD and PEG between continent and incontinent respondents.…”
Section: Resultsmentioning
confidence: 99%
“…Male partners of women with urinary incontinence also report lower sexual function and sexual satisfaction 166 . Overall, female urinary incontinence and urgency negatively affect sexual function in almost 50% of affected women and in 20% of their partners 167 .…”
Section: Quality Of Lifementioning
confidence: 99%